Pelatihan Sitasi dan Daftar Pustaka Format Turabian Style dengan Mendeley Desktop untuk Mahasiswa Baru - Zulvia Trinova; Sri Mulyono; Ai Siti Nurmiati; Jimmy Malintang; Yuanita Susanti (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This This training aimed to improve the understanding and skills of new students in writing citations and bibliographies using the Turabian style with Mendeley Desktop, using practical training methods and intensive mentoring. The training results demonstrated a significant improvement in participants' technical competency. Prior to the training, all new students reported difficulty distinguishing between Turabian footnote and bibliography formats and had never used a reference manager. After participating in an introductory session on Turabian style and a Mendeley installation practice, participants were able to input references manually and via PDF import. They also successfully used the Mendeley plugin in Microsoft Word to insert citations (footnotes) and automatically generate a bibliography. Evaluations showed that 95% of participants successfully compiled a bibliography correctly formatted according to Turabian guidelines, without errors in name order or punctuation. Participants reported increased confidence and efficiency in completing academic assignments that require rigorous source citations. This success confirms that the combination of technical training and practical mentoring is effective in equipping new students with essential information literacy and reference management skills throughout their studies.